(untitled) (AYUSHDHARA, 2021)
Ayurveda is the ancient holistic science of life which gives us most detailed information on different Ahara (Diet) and lifestyles to be followed in different disease conditions as well as to maintain the optimum health of a healthy human being. Ayurveda states in full detail about the specific Ahara and lifestyles to be followed during different seasons under different climate circumstances and for different diseases. Ayurveda has scientific approach in planning the Ahara; therefore Acharya Charaka has included Ahara as first among the three supporting pillars of life. Ahara is an important component for the management of a disease in the same way as Ahara is considered as an important aid to protect the life and health. Sthoulya (Obesity/Medoroga) is a burning problem in present era due to improper Ahara and luxurious and competitive lifestyle. People have neither time nor interested to follow the dietetic regimens as well as daily regimens and seasonal regimens as described in classical texts of the Ayurveda.